Analysis of Adaptive Evolution and Coevolution of rbcL Gene in the Genus Galdieria (Rhodophyta). (6th January 2021) - Han, Yuxin; Liu, Xudong; Nan, Fangru; Feng, Jia; Lv, Junping; Liu, Qi; Xie, Shulian
Abstract: To research the adaptive evolution and coevolution of the rbc L gene in the genus Galdieria, 36 sequences were selected. The bioinformatics of proteins encoded by rbc L genes of Galdieria were analyzed, and phylogenetic trees were constructed by the maximum‐likelihood method. Then, adaptive evolution and coevolution were analyzed. The phylogenetic tree showed that the inner groups were clustered into four branches, in which the sequences of Galdieria maxima were divided into two small branches, and the posterior probability of each branch is above 94.9%. Eleven reliable positive selection sites were detected in the branched‐site model, indicating that the rbc L protein‐coding gene of Galdieria underwent adaptive evolution to adapt to extreme environments. Site 269 F is located in the loop 6 domain, while sites 272 D and 273 W are located in the 6‐helix structure. Many coevolution pairs were detected, which were closely related to the hydrophobic and molecular weight correlation values of amino acids. The results are helpful to research the evolution process of freshwater red algae, to explore the changes of its essential genes and protein functions to adapt to different environmental pressures, and to understand the close relationship between amino acids in proteins and the molecular mechanism of evolution.